Mobile application for full-body sensing system - Soo, Kuan Yong (2019)
Wearable technology has developed rapidly over the years especially in the healthcare sector. One possible reason for this innovation is due to aging population and many are getting more health conscious. Majority of wearables found commonly in the market today are accessories. There is a need to introduce health care products embedded in necessities such as clothing. This project is to develop a mobile application which collects the data from a full-body sensing system, and vividly display the health situation. The system consists of sensors such as temperature, humidity, heart rate pulse sensors on the clothing. Hardware and software used in the creation of this project is documented in this report. A simulated system is created using Arduino Uno with several peripherals and Bluetooth Low Energy (BLE) module to communicate with the mobile application. Peripherals include temperature, humidity and heart rate pulse sensors to capture physiological signals to translate into health situation. Additional functions implemented in the mobile application on top of displaying health situation includes login capability for different account types such as user and administrator, edit personal particulars as a user, view past data displayed using line chart in the format of hours, days, weeks, months and years. As an administrator, view recently logged in users and user demographics by gender and age displayed in 2 pie charts respectively. Administrators have the flexibility to apply gender or age group filter for further understanding of the application user demographics. This project serves as a starting point for developers aiming to create mobile application that communicates with wearable smart clothing. This will help users understand their health conditions better and make necessary changes to their lifestyles and habits to improve their health. Further implementation of new functions can be included to this project to create a more intelligent, reliable and robust device.